Single stage bilateral uniportal videothoracoscopic sympathicotomy for hyperhidrosis: can it be managed as an outpatient procedure? - Ahmet Demirkaya; Ezel Erşen; Burcu Kılıç; Hasan Volkan Kara; Mehlika İşcan; Kamil Kaynak; Akif Turna (Videosurgery and Other Miniinvasive Techniques)
Introduction : The videothoracoscopic approach is minimally invasive with benefits that include less postoperative pain and shorter hospital stay. It is also a safe procedure which can be performed on an outpatient basis. Aim: To determine whether videothoracoscopic sympathicotomy can be performed safely in most patients as an outpatient procedure. Material and methods: Between July 2005 and October 2015, a total of 92 patients underwent bilateral and single port thoracoscopic sympathicotomy in our department on an outpatient basis. The level of sympathicotomy was T2 in 2 (2.2%) patients, T2 to T3 in 31 (33%) patients, T2 to T4 in 46 (50%) patients and T3 to T4 in 12 (13%) patients. Demographic data, length of postoperative stay, substitution index (SI), admission rate (AR) and readmission rate (RR), complications and patient satisfaction were reviewed retrospectively. Results: Two (2.2%) patients suffered from chest pain, while 4 (4.3%) patients complained about pain at the port site. Mean discharge time after surgery was 5.1 h (range: 4–6 h), mean duration of hospital stay was 0.15 days (0–3 days) postoperatively and the mean operation time was 43.6 min (15–130 min). In 8 (8.6%) patients, pneumothorax was detected on postoperative chest X-ray, while 5 (5.4%) patients required chest tube drainage. Mild or moderate compensatory sweating developed in 32 (34.7%) patients. No recurrence was observed, and the satisfaction rate was 96.7%. Substitution index and admission rate were 91.3% and 11% respectively, while RR was 0%. Conclusions : Bilateral video-assisted thoracoscopic sympathicotomy can be performed safely in most patients as an outpatient procedure.